Swearing Analysis of Characters in Possession Novel (1990) Written by As Byatt - Pratama Putra, Octa; Zuriyati, Zuriyati; Lustyantie, Ninuk (LPPM Universitas Pancasakti Tegal, 2021)
T This research focuses to identify the types and the reasons for swearing for characters of Possession Novel (1990). It uses a qualitative method to analyze the data. It has 81 data of types of swearing, and 83 data of reasons for swearing out of 83 data. The data of this research are in the form of utterances spoken by the characters in the novel. This research finds that the types of swearing uttered by the characters of Possession Novel (1990) can be classified into five types. According to Pinker (2010), there are Dyphemistic Swearing (DS), Abusive Swearing (AS), Idiomatic Swearing (IS), Emphatic Swearing (ES), and Cathartic Swearing (CS). In addition, the study also found the reasons for swearing consisting of three motives; Psychological Motives (PM), Social Motives (SM), and Linguistic Motives (LM). From this research, it can be concluded that emphatic swearing is the most used swearing expression and psychological motives are the most dominant reasons spoken by the characters.